Cyber-activism: Engendering Political Subjects within New Logics of Resistance in Contemporary Egypt and Yemen - Mansour, Fatma Abdulmalik (AUC Knowledge Fountain, 2016)
The purpose of this thesis is to study cyber-activism as a new social phenomenon in the context of the Arab revolutions particularly in Egypt and Yemen from two different perspectives. The first one is a global perspective in which I intend to situate this new social phenomenon called â€œcyberactivismâ€ in its spatial-temporal context in order to explore the following questions: What are the possibilities and the limitations of cyberactivism as a new site of resistance particularly in the context of Egypt and Yemen? To what extent can cyberactivism challenge the dominant logics which enabled the emergence to these possibilities within communicative capitalism? Are there new possibilities of resistance that exist within or outside these hegemonic logics? This thesis postulates that linking cyberactivism with capitalist production and labour relations is crucial to answer the previous questions given that the same production and reproduction processes structure define both social relations and these new technologies. Hence, cyberactivism, this thesis argues, constitutes a new site of resistance that has emerged out of these new hegemonic cognitive and immaterial practices of laboring. Secondly, this thesis explores cyberactivism as a new social phenomenon through a New Social Movements (NSM) perspective. It asks the following questions, can cyberactivism in the context of the so-called â€œArab Springâ€, particularly in Egypt and Yemen, be a new kind of social movement that can be studied and traced within the NSM framework? What are the potentials of such a perspective particularly in constructing new political subjects? In order to answer these questions this thesis engages and compares the NSM logics and theories with the nature and dynamics of the cyberactivism in an attempt to conceptualize a theoretical framework for this new phenomenon in order to further our understanding as well as capture its possibilities and limitations.